2016
DOI: 10.5755/j01.ee.27.5.15166
|View full text |Cite
|
Sign up to set email alerts
|

Cause-related marketing as a commercially and socially oriented activity: what factors influence and moderate the purchasing?

Abstract: Cause-related marketing uniquely integrates business objectives with social causes, thus simultaneously satisfying usual consumer needs and moral considerations to support social campaigns. As cause-related marketing (CRM) becomes more prevalent, companies will need to be more effective and efficient in launching cause-related marketing campaigns. Simply having a cause-related marketing campaign was once sufficient to distinguish a company; increasing competitiveness in this arena means that campaigns have to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
(99 reference statements)
0
13
0
Order By: Relevance
“…Altruism is a psychological trait via which individuals help others without seeking or receiving any external rewards, and it serves as a significant motivator behind volunteer work that provides aid to others [39]. In the context of cause-related marketing, altruism is considered a key factor in encouraging consumers to support social causes and to become socially responsible society members [40]. Given this, Patel et al [38] found that, when consumers have a positive attitude regarding a brand that realizes CRM, they show high purchase intention related to the brand, and the link between brand attitude and purchase intention becomes stronger if the consumers are more involved with the cause.…”
Section: Moderating Effects Of Altruismmentioning
confidence: 99%
“…Altruism is a psychological trait via which individuals help others without seeking or receiving any external rewards, and it serves as a significant motivator behind volunteer work that provides aid to others [39]. In the context of cause-related marketing, altruism is considered a key factor in encouraging consumers to support social causes and to become socially responsible society members [40]. Given this, Patel et al [38] found that, when consumers have a positive attitude regarding a brand that realizes CRM, they show high purchase intention related to the brand, and the link between brand attitude and purchase intention becomes stronger if the consumers are more involved with the cause.…”
Section: Moderating Effects Of Altruismmentioning
confidence: 99%
“…In general, altruism means an individual's intrinsic psychological tendency to help others without any external compensation [21]. Highly altruistic consumers tend to respond more positively to corporate social responsibility activities and care to help others more often than non-altruistic consumers [22]. For example, Lavack and Kropp [19] reported that consumers who are more interested in philanthropic activities value positive relationships with others and show a more positive attitude toward corporate social responsibility activities.…”
Section: Introductionmentioning
confidence: 99%
“…Not only do these personality features stimulate willingness to buy products from socially responsible companies (e.g. [Adomaviciute et al 2016;Webb, Mohr 1998]) but, as the research presented in this paper shows, they also enhance the willingness to pay a higher price for charity-linked products. Regarding consumer attitude toward social causes, Bagozzi [1979] deserves a mention.…”
Section: Resultsmentioning
confidence: 82%
“…While most studies around the economic results of CrM refer to the purchase intention, the author's own research is focused on WTP. In the face of growing interest in the CrM concept, both from practitioners and researchers [Natarajan et al 2016;Adomaviciute et al 2016], a gap is revealed in the research on its economic effects expressed in paying more. The emerging problem of sufficient knowledge regarding the determinants of a consumer's willingness to pay more for cause-related products 1 , including Polish realities, constitutes the main factor in favour of discussing the willingness to pay issue.…”
Section: Introductionmentioning
confidence: 99%